Accuracy of Cone-beam Computed Tomography in Comparing with Clearing and Staining Method in Evaluating the Root Canal Morphology: An In Vitro Study - Dalili Kajan, Zahra; Taramsari, Mehran; Khosravi Fard, Negar; Kanani, Mohsen (Iranian Endodontic Journal, 2018)
Introduction: In order to successfully perform root canal treatment, thorough knowledge of the root canal anatomy is essential. Cone-beam computed tomography (CBCT) has the ability to improve our understanding of the root canal system. The goal of the present study was to compare the accuracy of CBCT in revealing the number and form of the root canals of different maxillary and mandibular teeth with clearing and staining method. Methods and Materials: CBCT images were taken from 80 extracted human teeth fixed in agar arch models. The number and configuration of the root canals of each tooth were determined by the two observers. Then the teeth were cleared and stained. Two endodontists evaluated the number and forms of the root canals. The accuracy of CBCT was determined and compared with clearing and staining by Fisher’s exact test. The agreement of two methods in detection of the number and form of the root canals were evaluated by Kappa test, P≤0.05. Results: CBCT accurately detected the number of root canals in 129 (92.1%) of 140 roots and the form of the canals in 119 (85%) of the roots. There was no significant difference between the accuracy of CBCT in the detection of the number (P=0.13) and forms (P=0.4) of root canals of maxillary and mandibular teeth. The agreement between CBCT, and tooth clearing and staining in detection of the number of root canals was excellent in the maxilla (kappa=0.88±0.05) and good in the mandible (kappa=0.720±0.097). The agreement between the two methods in demonstration of the form of root canals was good in both maxillary (kappa=0.73±0.07) and mandibular (kappa=0.67±0.09) teeth. Conclusion: CBCT provides accurate information about root canal morphology. Application of this technique could result in more successful endodontic treatments. Keywords: Anatomy; Cone-beam Computed Tomography; Root Canals